Fiber Optic Sensor for Measuring Rotation - Al-Hilly, S M; Khaleel, Z E; Alrubaye, A F (Al-Nahrain Journal of Science, 2018)
The effect of the angular velocity on the interference pattern of Mach-Zehnder interferometer by using Sagnac effect had been investigated in this study. This interference pattern was produced from the interference of the two laser beams propagated through the two arms of the interferometer. The two arms consist of optical fiber wounded in circular shape. Each laser beam propagates in opposite direction to the other. When the system was rotated, a time difference between these two laser beams was produced. Different angular velocities (1.5°/sec,3°/sec,4.5°/sec, and 6°/sec ),different diameters of turns (0.22m,0.4m,0.6m,and 0.75m) and different lengths of optical fiber (2.8m,12.8m) were used to study the effect of each on the number of fringes .It has been found that any increase in each of the angular velocity, length of optical fiber and diameter of turns leads to an increase of the number of fringes.